2015
DOI: 10.1590/abd1806-4841.20152845
|View full text |Cite
|
Sign up to set email alerts
|

Black women’s hair: the main scalp dermatoses and aesthetic practices in women of African ethnicity

Abstract: Afro-ethnic hair is different from Caucasian and Asian hair and has unique features. Ethnic hair is more prone to certain conditions or diseases. Such diseases are not only related to the fragile inner structure of the hair, but also to the cultural habits of hairstyles that often exert traction forces upon the pilosebaceous follicle. Women with African hair subject their hair to chemical treatments such as hair straightening and relaxing, and thus modify the structure of their hair shaft, making it more susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
27
0
2
Order By: Relevance
“…It has been reported that the prognosis of TA is variable depending on how early the traction on the hair is stopped [14]. If the hair technique that exerts traction is stopped early, there can be reversal of the clinical phenotype; however, if traction continues for a prolonged period, chronic perifollicular inflammation may lead to permanent scarring alopecia [14]. We also found good agreement between the identification of extruded hair shafts and the presence of sebaceous glands.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It has been reported that the prognosis of TA is variable depending on how early the traction on the hair is stopped [14]. If the hair technique that exerts traction is stopped early, there can be reversal of the clinical phenotype; however, if traction continues for a prolonged period, chronic perifollicular inflammation may lead to permanent scarring alopecia [14]. We also found good agreement between the identification of extruded hair shafts and the presence of sebaceous glands.…”
Section: Discussionsupporting
confidence: 67%
“…This also alludes to the benefit of early diagnosis and reversal of TA-precipitating hair grooming and styling habits. It has been reported that the prognosis of TA is variable depending on how early the traction on the hair is stopped [14]. If the hair technique that exerts traction is stopped early, there can be reversal of the clinical phenotype; however, if traction continues for a prolonged period, chronic perifollicular inflammation may lead to permanent scarring alopecia [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean diameter of the hair samples was 0.10 ± 0.01 mm (Tables and ). Of note, upon three‐dimensional imaging, we found that Mestizo Mexican hair resembles Caucasian and Asian hair, in that hair shafts tend to be round‐shaped with homogenous diameters throughout the fibre, rather than elliptical, flattened and irregular, as seen with Afro‐ethnic hair (Figure ) …”
Section: Resultsmentioning
confidence: 91%
“…Although it seems to be a rare coincidence, the common background of traction as a possible main trigger of the three conditions points to the fact that in African-descent patients, trauma caused by the grooming habits and the use of hair extensions may be a frequent cause for the development of inflammation that can clinically be evident as one or more scalp abnormalities such as those presented in this work. The role of hair care practices in people of color and how it can influence the development of scalp diseases is particularly complex and may involve genetic predisposition [18,19]. …”
Section: Resultsmentioning
confidence: 99%